The association between ultra-processed foods intake and the odds of prostate cancer: a case–control study - Melika Mahmoudi-zadeh; Yahya Jalilpiran; Zahra Maghsoudi; Mehran Nouri; Shiva Faghih (Journal of Health, Population and Nutrition)
Abstract Background Ultra-processed foods (UPFs) are characterized by poor nutritional composition and the generating neo-formed carcinogens during high levels of processing. The current study aimed to investigate the association between UPFs consumption and the odds of prostate cancer (PC). Methods This case–control study recruited 62 PC cases and 63 hospital-based controls from two major referral hospitals of Shiraz, Iran, in 2015. Eligible men, newly diagnosed with PC through histological confirmation, were included as cases. Along with demographic and anthropometric information data, participant’s dietary intake was assessed using a semi-quantitative food frequency questionnaire. The NOVA classification was employed to categorize food items based on their level of industrial processing. The association between UPFs consumption (as a percentage of daily calorie intake) and the odds of developing PC was estimated using logistic regression models. BMI, education, physical activity, age, and fiber intake were considered confounders in the adjusted model. Results The study included 60 cases and 60 controls, with mean UPFs intake of 8.3% and 6.4%, respectively. The crude analysis showed no significant association between UPFs intake and PC odds ratio (OR) (OR = 1.96, confidence interval (CI) 95%: 0.94–4.05, P = 0.069). However, after adjusting for potential confounders, the association became significant, with high versus low UPFs intake associated with 2.81 times higher odds of PC (OR = 2.81, CI 95%: 1.18–6.65, P = 0.019). Conclusion Our findings highlight UPFs consumption as a factor associated with higher odds of PC in the Iranian male population. The study emphasizes the importance of monitoring industrial food processing practices and implementing measures to reduce UPFs consumption.